Safety Assement of Jambal Roti Salted Fish in Solo City - Nanik Suhartatik, Viandra Choirunissa, Merkuria Karyantina & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
Salted fish is one of the common processed fish, such as Ariidae Fish can be processedinto Jambal Roti. Salted fish which made by traditional processing will affect the qualityand safety of food. The criteria of safe food was the presence or absence of hazardouscomponents either physical, chemical and microbiological. This study aimed todetermine the water content, formalin content, salt content, total plate count,Escherichia coli, and Salmonella sp from salted fish jambal roti that sold in Solo City.The results of formalin test showed that 21 samples (87.5%) are containedformaldehyde. Salt content in salted fish are range from 4 to 16.9% and it was still lowerthan the SNI that was set salt content in salted fish by 20%. Water determination resultsshowed 23 samples (95.83%) have higher water content than SNI obligation which was40%. Total plate count showed that 1 sample was known upper than the SNI maximumstandard was 1. 105 CFU/g. Salmonella sp on Salted fish was negative whether E. colitest report that 25% of the samples were contain Escherichia coli.Keywords: E.coli, formaldehyde, salted fish, Salmonella sp, TPC